AWARENESS REGARDING TOBACCO SMOKING AMONG DENTAL HOUSEOFFICERS AND STAFF OF PRIVATE MEDICAL UNIVERSITY - Mawish Bano (Baqai Journal of Health Sciences)
Objective: The main objective of this study wasto determineawareness regarding tobacco smoking as well as prevalence among dental house officers, teaching and non-teaching staff. Method: This cross sectional study was designed in Baqai Dental College, Baqai Medical University. This study was completed by three different designated people of dental department (dental house officers, teaching and non-teaching staff.).The duration of study in which the survey of study conducted was of 6 months.The survey study was designed on close ended questionnaire consisted of personal and professional profile i.e. age, gender and designation, and few questions of survey based on knowledge and awareness regarding tobacco usage and smoking hazard. Result: The majority of the participants (92.9%) were aware that smoking causes serious diseases where as (89.7%) agreed that smoking should be prohibited in public places. There were (76.2%) participants who believed that providing nicotine cessation counselling is an important element of their job as a dental practitioner, and 59.5% believed that they are well prepared to assist patients in quitting smoking. The 81.7%of participants feltconfident in their ability to explain the harmful effects of cigarette use. Conclusion: Governments can reduce the number of people who smoke by imposing higher taxes on tobacco products, launching ongoing social media campaigns, mandating that doctors regularly advise smokers to give up and offer support while they do so, and granting access to medication and behavioral support for quitting.